Migration, Security and Law: the Challenge of Human Rights and Cultural Diversity - Cunha, Guilherme; Szlovik, Maeva (Pécs journal of international and European law, 2015)
Border control is fundamental to the existence of a State. The borders of a territory are of maximum importance to both public administration and national security. However, frequently these two realities are in conflict, when migration is investigated, during times of peace or conflict. It is intended to analyze to what extent the concepts of national security and border clash with the observation of human rights, especially for migrants.